Signaling via toll-like receptor 4 and CD40 in B cells plays a regulatory role in the pathogenesis of multiple sclerosis through interleukin-10 production. (March 2018) - Okada, Yoichiro; Ochi, Hirofumi; Fujii, Chihiro; Hashi, Yuichiro; Hamatani, Mio; Ashida, Shinji; Kawamura, Kazuyuki; Kusaka, Hirofumi; Matsumoto, Sadayuki; Nakagawa, Masanori; Mizuno, Toshiki; Takahashi, Ryosuke; et al.
Abstract: Background: B cells play an important role in the development of multiple sclerosis (MS), but can also exhibit regulatory functions through IL-10 production. Toll-like receptors (TLR) and CD40 signaling are likely to be involved in this process. Objective: To investigate the ability of MS B cells to produce IL-10 in response to TLR stimulation in the presence or absence of CD40 co-stimulation. Methods: Peripheral blood mononuclear cells obtained from 34 MS patients and 24 matched healthy participants (HS) were stimulated through either TLR4 or TLR9 alone, or together with CD40. Intracellular cytokine production was analyzed by flow cytometry. Results: The frequency of IL-10-producing cells in total B cells after either TLR9 or CD40 stimulation was significantly lower in MS than HS, regardless of disease phase. The frequency of IL-10 producing B cells after TLR4 stimulation did not differ significantly between HS and MS, regardless of disease phase. TLR4 and CD40 co-stimulation synergistically increased the frequency of IL-10-producing but not pro-inflammatory cytokine-producing B cells at MS relapse. This effect was observed in both CD27 − naïve and CD27 + memory B cells. The frequency of IL-10-producing B cells following CD40 stimulation was significantly higher in interferon-β responders than non-treated MS patients. Finally, we confirmed that the frequency of IL-10-producing B cells positively correlated with IL-10 production quantity by B cells using magnetic-isolated B cells. Conclusions: Cross-talk between TLR4 and CD40 signaling plays a crucial role in regulating IL-10 production by B cells during MS relapses, which may promote recovery from relapse. CD40 signaling in B cells is involved in the response to interferon-β in MS. Collectively, TLR4 and CD40 signaling in B cells may provide a promising target for MS therapy. Highlights: TLR9-and CD40-mediated IL-10 production by B cells was dysregulated in MS. TLR4-mediated IL-10 production by B cells was restored to the normal level in MS. Co-stimulation of TLR4 and CD40 enhanced IL-10 production by B cells at MS relapse. Cross-talk between TLR4 and CD40 signaling may promote recovery from MS relapse. Efficacy of IFN-β therapy relates to CD40-mediated IL-10 production by B cells in MS.